(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay examines the relation between human rights, the right to health, bio-ethics questions and religious freedom. After some preliminary remarks on methodological issues, the paper focuses on the difficulty of understanding the importance of religions in bioethical issues. The paper aims to proffer observations on the relevance of religion to full and “universal” protection of health protection for all, regardless of religious affiliation and the meanings that this implies.